1993
DOI: 10.7567/jjaps.32s2.383
|View full text |Cite
|
Sign up to set email alerts
|

Desorption, Dissociation and Orientation of Oxygen Admolecules on a Reconstructed Platinum(110)(1×2) Surface Studied by Thermal Desorption and Near-edge X-ray-Absorption Fine-Structure

Abstract: The desorption, dissociation and orientation of oxygen admolecules on a reconstructed Pt(110)(1×2) were studied by means of TDS combined with isotope tracer, NEXAFS, and angle-resolved TDS. The admolecules below half a monolayer lie on the bottom of the trough, being oriented along it. The molecules adsorbed additionally are lying on declining terraces. The desorption flux of the former species shows a simple cosine distribution, suggesting that the molecule is not localized on the bottom in the desorption eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…Both NEXAFS 22,26 and ARPES 25 identified a species aligned in the [11 h0] direction and lying parallel to the bulk surface plane of Pt{110}(1 × 2). Furthermore, the NEXAFS study was able to relate this species to the TDS peak observed at 200 K. 21 The identification of the ridge-bridge site (A) as the most stable adsorption site, based on the current calculations, is consistent with this empirical observation, since for adsorption in this site the internuclear axis is indeed orientated along the close-packed rows in the [11 h0] direction and parallel to the bulk surface plane.…”
Section: Energetics Of O 2 Adsorption On Pt{110}(1 × 2)mentioning
confidence: 98%
See 2 more Smart Citations
“…Both NEXAFS 22,26 and ARPES 25 identified a species aligned in the [11 h0] direction and lying parallel to the bulk surface plane of Pt{110}(1 × 2). Furthermore, the NEXAFS study was able to relate this species to the TDS peak observed at 200 K. 21 The identification of the ridge-bridge site (A) as the most stable adsorption site, based on the current calculations, is consistent with this empirical observation, since for adsorption in this site the internuclear axis is indeed orientated along the close-packed rows in the [11 h0] direction and parallel to the bulk surface plane.…”
Section: Energetics Of O 2 Adsorption On Pt{110}(1 × 2)mentioning
confidence: 98%
“…Whether oxygen adsorbs associatively or dissociatively on this surface depends on the substrate temperature. Ohno et al 21,22 determined on the basis of thermal desorption spectroscopy (TDS) and isotope tracer studies that, at temperatures below 180 K, oxygen adsorbs associatively, with dissociation of the admolecules taking place in the temperature range of 180-220 K. Recombinant desorption of oxygen adatoms was observed above 650 K.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have observed O 2 on Pt(110), which exhibits a missing row (1 × 2) reconstruction, at temperatures below 133 K. ,, At low coverage (<1/2 ML), O 2 appears to adsorb in the bridge site between two top-layer Pt atoms, with the axis along the Pt row. (An early study identified the bottom of the trough as the adsorption site, based on a mistaken assumption concerning the site preference of Xe.…”
Section: Molecularly Adsorbed O2 States On Particular Surfacesmentioning
confidence: 99%
“…O 2 dissociation is thought to be precursor mediated on Pt(110), consistent with the clear identification of an adsorbed O 2 species at low temperatures. Dissociation begins around 125 K and is complete by 200–220 K, such that adsorption at higher temperatures is dissociative. ,,, Short-lived O 2 species can interact directly with adsorbed C, suggesting that O 2 dissociation can be mediated by coadsorbates. , Under strongly oxidizing conditions, a surface oxide can form. ,, …”
Section: Mechanisms and Barriers For O2 Dissociationmentioning
confidence: 99%